Pengaruh Pengawasan dan Komitmen Organisasi Terhadap Kinerja Pegawai di Kantor Kementerian Agama Kota Lubuklinggau - Amelia, Yolanda; Ronal Aprianto; Suyadi, Suyadi (MAMEN: Jurnal Manajemen, 2022)
The purpose of this study was the effect of supervision and organizational commitment on employee performance at the Ministry of Religion Office of Lubuklinggau City. The formulation of the problem of this research is whether supervision and organizational commitment on employee performance at the Ministry of Religion Office of Lubuklinggau City. The population and samples used were 53 employees. This study uses quantitative research methods. The results obtained 1) Supervision has a positive and partially significant effect on employee performance with tcount = 4.905 > ttable = 1.674 significant 0.000 <0.05. 2) Organizational Commitment has a partially significant positive effect on employee performance with tcount = 5.060 > ttable = 1.674 significant 0.000 <0.05. 3) Supervision and Organizational Commitment have a significant positive effect simultaneously on Employee Performance with Fcount = 18.127 > Ftable = 3.18 significant 0.000 <0.05. The conclusion is that supervision and organizational commitment have a positive and significant effect partially and simultaneously on employee performance at the Ministry of Religion Office of Lubuklinggau City.